Peran Perikanan Tangkap dalam Mewujudkan Ketahanan Pangan: Suatu Kajian Sosiologis The Role of Catch Fisheries in Creating Food Security: A Sociological Study - Harahap, Rahma Hayati; Putri, Nurul Inayah (Talenta Publisher, 2024)
The existence of marine fish in Indonesian waters is very abundant and will continue to provide benefits as long as it is managed properly. Marine fish that act as a source of animal protein can be utilized through the fishing process. The agriculture, forestry, and fisheries sectors are the main pillars of GDP at 23.01 percent. The East Coast region contributed the most, namely 74.73% or around 717.04 trillion rupiah to the GDP of North Sumatra. Bagan Percut is one of the potential areas in North Sumatra for efforts to develop the non-port fisheries subsector. Therefore, the social capital of fishing fishermen to be able to realize food security at the local level is important to be studied. This study aims to analyze the role of capture fisheries in realizing food security with sociological theory. This research uses a qualitative approach. The results showed that capture fisheries play a role in realizing food security in three pillars, namely availability, affordability, and utilization. Fishermen play an important role in fish production, agents play a role in distributing catches, and households play a role in food utilization. During the lean season, fishing households can maintain food security by utilizing social capital through the Serikat Tolong Menolong (STM), officers, and cooperatives. In conclusion, from the economic side, capture fisheries contribute to regional income and fishermen's source of income. From the social side, fishermen and agents/distributors must have social capital to support capture fisheries activities in realizing food security.